2015
DOI: 10.1093/jxb/eru516
|View full text |Cite
|
Sign up to set email alerts
|

Wounding tomato fruit elicits ripening-stage specific changes in gene expression and production of volatile compounds

Abstract: SummaryAs tomato fruit ripen, the wounding-elicited transcriptome and VOC profiles alter. This shift is consistent with a change from protection of developing seeds to attraction of frugivores for seed dispersal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 75 publications
1
21
1
Order By: Relevance
“…Therefore, the identification of suitable RGs for specific experimental conditions is essential for avoiding unnecessary error in the qRCR experimental results. So far, many studies involving the identification or evaluation of tomato RGs under various experimental conditions, including biotic/abiotic stresses ( Cucumber mosaic virus, tobacco mosaic virus, bacterium Xanthomonas campestris , nitrogen stress, cold, light stress) (Coker and Davies, 2003 ; Løvdal and Lillo, 2009 ; Mascia et al, 2010 ; Wieczorek et al, 2013 ; Müller et al, 2015 ) and different organs/tissues (Leaf, fruit, flower, and seed) (Exposito-Rodriguez et al, 2008 ; Dekkers et al, 2012 ; Gao et al, 2012 ; Baldassarre et al, 2015 ), had been conducted. For example, SlACT, SlCAC , and SlEF1 α were validated to be suitable RGs in studies of host-virus interactions in tomato (Wieczorek et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the identification of suitable RGs for specific experimental conditions is essential for avoiding unnecessary error in the qRCR experimental results. So far, many studies involving the identification or evaluation of tomato RGs under various experimental conditions, including biotic/abiotic stresses ( Cucumber mosaic virus, tobacco mosaic virus, bacterium Xanthomonas campestris , nitrogen stress, cold, light stress) (Coker and Davies, 2003 ; Løvdal and Lillo, 2009 ; Mascia et al, 2010 ; Wieczorek et al, 2013 ; Müller et al, 2015 ) and different organs/tissues (Leaf, fruit, flower, and seed) (Exposito-Rodriguez et al, 2008 ; Dekkers et al, 2012 ; Gao et al, 2012 ; Baldassarre et al, 2015 ), had been conducted. For example, SlACT, SlCAC , and SlEF1 α were validated to be suitable RGs in studies of host-virus interactions in tomato (Wieczorek et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exposito-Rodriguez et al ( 2008 ) found that the widely used RGs, such as SlCAC, SlTIP41, Expressed , and SlSAND , provide superior transcript normalization in various tissues of tomato (Exposito-Rodriguez et al, 2008 ). When studying the changes of gene expression in the wounded ripening-stage tomato fruit, Baldassarre et al ( 2015 ) selected two most stably expressed RGs ( EF1- α and GADPH ) from seven routine used HKGs for normalization in the subsequent qPCR analysis. Thus, it occurred to us that although tomato is regarded as model plant for fruit development study, little attention has yet been paid to screen the best RGs specifically for normalization during the development of tomato fruit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their concentrations will dramatically and spatiotemporally change during growing and ripening processes [ 1 3 ]. Both biotic and abiotic stresses also trigger concentration changes, which lead to whole-tissue physiological changes, such as alterations in color and taste during the ripening process, or more local and partial responses, such as morphological changes induced by wounding and pest-associated stresses [ 4 , 5 ]. These events are strictly regulated, and alterations in metabolic dynamics occur as the result of a wide range of biochemical processes, including enzymatic or non-enzymatic reactions [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%